Rates and risk factors for migraine progression using multiple definitions of progression: Results of the longitudinal OVERCOME (US) study - Buse, Dawn C.; Muenzel, E. Jolanda; Zagar, Anthony J.; Mehrabadi, Ali Sheikhi; Shapiro, Robert E.; Kim, Gilwan; Ashina, Sait; Nicholson, Robert A.; Lipton, Richard B. (Headache, 2025)
Objective To estimate rates of migraine progression and assess predictors of progression in a large, longitudinal cohort study using the traditional definition and two alternative definitions of migraine progression. Background Traditionally, migraine progression is defined as moving from episodic migraine (EM) with ≤ 14 monthly headache days (MHD) to chronic migraine (CM) with ≥ 15 MHDs of which 8 are attributable to migraine. This definition does not take into account changes in the full range of potential headache days, disability, or impact on function. Methods The Observational Survey of the Epidemiology, Treatment, and Care of Migraine (OVERCOME) study identified, characterized, and followed a representative sample of adults with migraine in the United States. Migraine was defined based on the International Classification of Headache Disorders, 3rd edition (ICHD‐3) criteria. We estimated rates of migraine progression at 1 year of follow‐up using three definitions: (1) traditional EM‐to‐CM transition, (2) increase of ≥ 5 MHDs (MHD progression), and (3) increase of ≥ 5 points on the Migraine Disability Assessment (MIDAS) scale (MIDAS progression). The analysis identified sociodemographic, clinical, and migraine‐related characteristics associated with each definition of progression from a set of 67 candidates and then determined the association with progression for each candidate predictor and each definition of progression. Results A total of 11,634 participants met ICHD‐3 criteria for migraine at baseline and completed the 1‐year follow‐up survey. The average age was 48.2 years, and average years living with migraine was 22.8 years. The sample was 75.6% female (8793/11,634), 84.4% White (9814/11,634), 6.5% Black (757/11,634), and 7.6% Hispanic (889/11,634). The majority (89.2%, 10,374/11,634) had EM at baseline, and among these, 4.7% progressed to CM over 1 year of follow‐up. Rates of progression at 1 year were higher using other definitions of progression, with 9.6% (1087/11,329) reporting an increase in ≥ 5 MHDs and 21.7% (2519/11,630) reporting an increase of ≥ 5 MIDAS points. Across all three definitions of progression, ever taking preventive medications for migraine placed people at lower odds of progressing (odds ratio [95% confidence interval]: EM‐to‐CM transition, 0.7 [0.57–0.85]; MHD progression, 0.9 [0.75–1.00]; MIDAS progression, 0.8 [0.73–0.91]), while the presence of depression placed people at higher odds of progressing (odds ratio [95% confidence interval]: EM‐to‐CM transition, 1.3 [1.05–1.69]; MHD progression, 1.4 [1.21–1.67]; MIDAS progression, 1.2 [1.04–1.34]). Conclusion This work expands the concept of migraine progression, exploring two alternative definitions that modify the potential range of MHD changes and take disability into account. This analysis identified never having used preventive medications for migraine and presence of depression as risk factors across all three definitions of progression. This work may more accurately identify persons with progression and at risk of migraine progression, setting the stage for trials of preventive intervention and ultimately more effective practice. Plain Language Summary In this study, we used machine learning to examine rates and risk factors for migraine progression using the traditional definition: new onset of chronic migraine with ≥ 15 monthly headache days on average, as well as two novel additional definitions: (1) increase of ≥ 5 monthly headache days and (2) increase in Migraine Disability Assessment (MIDAS) scale of ≥ 5 points. Never having used preventive medication and presence of depression were identified as risk factors for migraine progression across all three definitions of migraine progression. These novel additional definitions of migraine progression may provide new clinical trial endpoints, inform inclusion criteria for clinical trials, and offer insights into prognosis and clinical care.